Cell wall integrity modulates Arabidopsis thaliana cell cycle gene expression in a cytokinin- and nitrate reductase-dependent manner - Gigli-Bisceglia, Nora; Engelsdorf, Timo; Strnad, Miroslav; Vaahtera, Lauri; Khan, Ghazanfar Abbas; Yamoune, Amel; Alipanah, Leila; Novák, Ondřej; Persson, Staffan; Hejatko, Jan; Hamann, Thorsten (Development (Cambridge, England), 2018)
During plant growth and defense, cell cycle activity needs to be coordinated with cell wall integrity. Little is known about how this coordination is achieved. Here, we investigated coordination in Arabidopsis thaliana seedlings by studying the impact of cell wall damage (CWD, caused by cellulose biosynthesis inhibition) on cytokinin homeostasis, cell cycle gene expression and cell shape in root tips. CWD inhibited cell cycle gene expression and increased transition zone cell width in an osmosensitive manner. These results were correlated with CWD-induced, osmosensitive changes in cytokinin homeostasis. Expression of CYTOKININ OXIDASE/DEHYDROGENASE 2 and 3 (CKX2, CKX3), which encode cytokinin-degrading enzymes, was induced by CWD and reduced by osmoticum treatment. In nitrate reductase1 nitrate reductase2 (nia1 nia2) seedlings, CKX2 and CKX3 transcript levels were not increased and cell cycle gene expression was not repressed by CWD. Moreover, established CWD-induced responses, such as jasmonic acid, salicylic acid and lignin production, were also absent, implying a central role of NIA1/2-mediated processes in regulation of CWD responses. These results suggest that CWD enhances cytokinin degradation rates through a NIA1/2-mediated process, leading to attenuation of cell cycle gene expression.
Keywords: sorbitol; homeostáza; biologické modely; Phenotype; Arabidopsis Proteins; osmóza; Cell Cycle; nitrátreduktasa; Models, Biological; Homeostasis; Cell wall signaling; messenger RNA; cytokininy; Cytokinins; proteiny huseníčku; buněčný cyklus; RNA, Messenger; Benzamides; Cellulose biosynthesis; Plant Roots; benzamidy; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; buněčná stěna; Nitrate reductase; Osmosis; Arabidopsis; fenotyp; Nitrate Reductase; semenáček; Seedlings; kořeny rostlin; Cell wall integrity; Cytokinin; Cell Wall; Sorbitol; Cell cycle